Pengaruh PDRB, Populasi, Kurs dan Inflasi terhadap Impor di Sumatera Utara pada Tahun 2001-2017 - Sundari, Emi; Ruslan, Dede; Hidayat, Paidi (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
This study aimed to examine the impact of several independent variables—namely Gross Regional Domestic Product (GRDP), Population, Exchange Rate, and Inflation—on the dependent variable, Imports in North Sumatra, during the period from 2001 to 2017. The research adopted a quantitative approach, utilizing secondary data as the primary source. The sample consisted of time series data from 2001 to 2017, sourced from publications by the Central Statistics Agency (BPS) of North Sumatra. Data analysis was carried out using the Ordinary Least Squares (OLS) method, with SPSS 20 as the data processing tool.The findings of the study indicate that, collectively, GRDP, Population, Exchange Rate, and Inflation have a significant simultaneous effect on imports in North Sumatra Province during the observed period. Partial tests reveal that GRDP, Population, and Inflation each have a positive and significant influence on imports, whereas the Exchange Rate is negatively and significantly associated with imports in North Sumatra. The combined explanatory power of GRDP, Population, Exchange Rate, and Inflation accounts for 94.5% of the variation in imports, with the remaining 5.5% attributed to other factors not included in the model.